Global War, Global Catastrophe Neutrals, Belligerents and the Transformations of the First World War - Abbenhuis, Maartje (New Approaches to International History, 2021)
Winner of the World War One Historical Association's 2021 Norman B. Tomlinson, Jr. Prize Global War, Global Catastrophe presents a history of the First World War as an all-consuming industrial war that forcibly reshaped the international environment and, with it, impacted the futures of all the world's people. Narrated chronologically, and available open access, the authors identify key themes and moments that radicalized the war's conduct and globalized its impact, affecting neutral and belligerent societies alike. These include Germany's invasion of Belgium and Britain's declaration of war in 1914, the expansion of economic warfare in 1915, anti-imperial resistance, the Russian revolutions of 1917 and the United States' entry into the war. Each chapter explains how individuals, communities, nation-states and empires experienced, considered and behaved in relationship to the conflict as it evolved into a total global war. Above all, the book argues that only by integrating the history of neutral and subject communities can we fully understand what made the First World War such a globally transformative event. This book offers an accessible and readable overview of the major trajectories of the global history of the conflict. It offers an innovative history of the First World War and an important alternative to existing belligerent-centric studies. The ebook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.